Measures of eating disorder symptoms, drive for muscularity, and muscle dysmorphia: Norms and typologies of Australian men. (5th November 2015) - Hughes, Elizabeth K.; Dean, Cassandra; Allen, J. Sabura
Abstract: Objective: The study aimed to provide normative data on measures of eating disorder symptoms, drive for muscularity, and muscle dysmorphia in men, and to identify typologies based on these measures. Method: A community sample of 284 Australian men (19–84 years) completed the Eating Attitudes Test‐26, Eating Disorder Examination‐questionnaire, Clinical Impairment Assessment Questionnaire, Drive for Muscularity Scale, and Muscle Dysmorphia Inventory. Internal consistency, means, standard deviations, and percentile ranks were calculated for each measure, and results were compared with published findings on men from North America and Germany. A cluster analysis was also conducted. Results: Internal consistency was adequate to excellent across most measures, and scores were similar to those of men in other countries. Cluster analysis identified three typologies: men with high muscularity, shape, and weight concerns as well as high dieting and exercise dependence; men with moderate shape and weight concerns, moderate muscularity concerns, and high dieting; and men with low to moderate scores across all measures. Conclusions: The normative data provided will be an important resource for researchers and clinicians needing to utilise and interpret measures of eating disorder, muscle dysmorphia, and drive for muscularity with men. In addition, the typologies identified suggest that when assessing men attention should be paid to attitudes and behaviours related to both drive for muscularity and drive for thinness.